SIRT1 is required for AMPK activation and the beneficial effects of resveratrol on mitochondrial function - Price, Nathan L; Gomes, Ana P; Ling, Alvin J Y; Duarte, Filipe V; Martin-Montalvo, Alejandro; North, Brian J; Agarwal, Beamon; Ye, Lan; Ramadori, Giorgio; Teodoro, Joao S; Hubbard, Basil P; Varela, Ana T; et al. (Cell metabolism, 2012)
Resveratrol induces mitochondrial biogenesis and protects against metabolic decline, but whether SIRT1 mediates these benefits is the subject of debate. To circumvent the developmental defects of germline SIRT1 knockouts, we have developed an inducible system that permits whole-body deletion of SIRT1 in adult mice. Mice treated with a moderate dose of resveratrol showed increased mitochondrial biogenesis and function, AMPK activation, and increased NAD(+) levels in skeletal muscle, whereas SIRT1 knockouts displayed none of these benefits. A mouse overexpressing SIRT1 mimicked these effects. A high dose of resveratrol activated AMPK in a SIRT1-independent manner, demonstrating that resveratrol dosage is a critical factor. Importantly, at both doses of resveratrol no improvements in mitochondrial function were observed in animals lacking SIRT1. Together these data indicate that SIRT1 plays an essential role in the ability of moderate doses of resveratrol to stimulate AMPK and improve mitochondrial function both in vitro and in vivo.